Exploring validation of a graphic symbol questionnaire to measure participation experiences of youth in activity settings. (3rd April 2017) - Batorowicz, Beata; King, Gillian; Vane, Freda; Pinto, Madhu; Raghavendra, Parimala
Abstract: Participation has a subjective and private dimension, and so it is important to hear directly from youth about their experiences in various activity settings, the places where they "do things" and interact with others. To meet this need, our team developed the Self-Reported Experiences of Activity Settings (SEAS) measure, which demonstrated good-to-excellent measurement properties. To address the needs of youth who could benefit from graphic symbol support, the SEAS-PCS TM, 1 was created. The purpose of this paper is to describe the development of SEAS-PCS and the preliminary study that explores the equivalency of the SEAS and SEAS-PCS. The SEAS and SEAS-PCS were compared in terms of the equivalency of meaning of stimulus items by 11 professionals and five adults who used augmentative and alternative communication, were familiar with PCS, and were fluent readers. Out of 22 items, 68% were rated as highly similar on a 5-point scale ( M  = 4.14; SD  = .70; mdn  = 4; range: 2.81–5.00). Subsequently, the 32% of the SEAS-PCS items that were rated below 4 were modified based on the participants' specific comments. Further work is required to validate the SEAS-PCS. The next step could involve exploring the views of youth who use AAC.